Effect of skin coatings on prolonging shelf life of kagzi lime fruits (Citrus aurantifolia Swingle) - Bisen, Abhay (Springer-Verlag, 2011)
An experiment was conducted to assess the influence of chemical and oil coatings on storage life of kagzi lime fruits. Fruits were harvested at physiological light green mature stage and treated with different concentrations of chemicals viz., Cacl(2) and KMnO(4) and edible coatings viz., (coconut oil, mustard oil, sesamum oil, castor oil and liquid paraffin wax). After treatment, fruits were kept at ambient condition (25–30 °C, 60–70% RH) till 18 days and analyzed for various physical and chemical parameters like PLW, marketable fruits retained, TSS, acidity, ascorbic acid, juice content and also organoleptic values. The results revealed that edible oil emulsion coating particularly coconut oil had significantly (p ≤ 0.05) effect on reduction of the physiological loss in weight (9.67%) and maximum marketable fruits retained (70%), total soluble solids (8.43%), ascorbic acid (49.93 mg/100 ml juice), acidity (1.52%) and juice content (42.34%) of fruits. Similarly, application of this oil emulsion coating acceptable for sensory quality parameters such as appearance, flavour, taste, external colour and no incidence of moulds & their growth up to 18 days of storage.